Medication errors in anesthesia: unacceptable or unavoidable? - Dhawan,Ira (2017)
Abstract Medication errors are the common causes of patient morbidity and mortality. It adds financial burden to the institution as well. Though the impact varies from no harm to serious adverse effects including death, it needs attention on priority basis since medication errors' are preventable. In today's world where people are aware and medical claims are on the hike, it is of utmost priority that we curb this issue. Individual effort to decrease medication error alone might not be successful until a change in the existing protocols and system is incorporated. Often drug errors that occur cannot be reversed. The best way to ‘treat' drug errors is to prevent them. Wrong medication (due to syringe swap), overdose (due to misunderstanding or preconception of the dose, pump misuse and dilution error), incorrect administration route, under dosing and omission are common causes of medication error that occur perioperatively. Drug omission and calculation mistakes occur commonly in ICU. Medication errors can occur perioperatively either during preparation, administration or record keeping. Numerous human and system errors can be blamed for occurrence of medication errors. The need of the hour is to stop the blame - game, accept mistakes and develop a safe and ‘just' culture in order to prevent medication errors. The newly devised systems like VEINROM, a fluid delivery system is a novel approach in preventing drug errors due to most commonly used medications in anesthesia. Similar developments along with vigilant doctors, safe workplace culture and organizational support all together can help prevent these errors.